2114: The role of estrogen receptor-β in the development of the early endometriotic lesion. Issue 1 (10th May 2018) - Knudtson, Jennifer; Liu, Ya-Guang; Tellez Santos, Marlen; Tekmal, Rajeshwar; Vadlamudi, Ratna; Schenken, Robert
Abstract : OBJECTIVES/SPECIFIC AIMS: To further elucidate the role of estrogen receptor β (ER-β) in the early endometriotic lesion attachment. METHODS/STUDY POPULATION: EECs were immortalized using a telomerase vector. Immortalized cells and parental cells were characterized by genotyping, and expression of ER-β as well as other epithelial cell markers. ER-β was knocked-down in immortalized EECs using lentivirus-mediated shRNA transduction. ER-β knockdown was confirmed by RT-qPCR and Western analysis. EEC cells with or without ER-β knockdown were used to assess their attachment to PMCs in an established in vitro assay (Lucidi, 2005). Results were analyzed with Student t -test. RESULTS/ANTICIPATED RESULTS: Genotyping using karyotype assay confirmed a normal chromosomal profile. Also positive staining for cytokeratin and lack of any staining with vimentin confirms the epithelial origin of these cells. ER-β knockdown has a significant decrease in attachment compared to control ( p =0.02). DISCUSSION/SIGNIFICANCE OF IMPACT: Primary and immortalized cells were 46XX, cytokeratin positive, and vimentin negative confirming their epithelial origin. ER-β knockdown has a significant decrease in attachment compared with control.